The Valley of Flowers - Bachkheti, N. D. (Indian Forester, 1986)
Valley of Flowers is situated in main valley of Alakananda and Dhauli Ganga, in the Zaskar ranges of the Garhwal Himalayas. The paper comprehensively deals with the various aspects of the most beautiful place on earth. The valley is full of numerous flowers during different months.